Guillain–Barré syndrome associated with immune checkpoint inhibitors exposure: a pharmacovigilance study - Cabon, Jean; Ducloie, Mathilde; Chrétien, Basile; Arnaud, Charlotte; Alexandre, Joachim; Dolladille, Charles; Silva, Angélique Da (Journal of Neurology, 2025)
Guillain-Barré syndrome (GBS) is a life-threatening condition that has been associated with exposure to immune checkpoint inhibitors (ICIs); however, available data remain limited. We conducted a retrospective, worldwide, observational analysis of individual case safety reports in VigiBase, the World Health Organization’s pharmacovigilance database. To minimize competition bias, we excluded reports of vaccines and infectious associated with a known or potential risk of GBS. Subsequently, we searched for reports of GBS linked to ICI regimens, whether as monotherapy or dual immunotherapy, from the Food and Drug Administration (FDA) approval date of each agent until 12 February 2024. The primary endpoint of this study was to assess the association between GBS reporting and exposure to ICI regimens (either monotherapy or dual immunotherapy) using disproportionality analysis. This analysis was performed utilizing the Information Component (IC) and its 95% credibility interval lower boundary (IC 025 ). A total of 412 cases of GBS associated with ICIs were reported in VigiBase. The disproportionality analysis revealed a significant reporting signal between GBS and the anti-CTLA-4 and anti-PD-1 combination therapy (n = 102, IC 025 = 4.6), specifically with nivolumab and ipilimumab (n = 100, IC 025 = 4.6); anti-CTLA-4 monotherapy (n = 39, IC 025 = 3.6) with ipilimumab monotherapy (n = 39, IC 025 = 3.6); anti-PD-1 monotherapy (n = 217, IC 025 = 3.4), including pembrolizumab (n = 124, IC 025 = 3.5), nivolumab (n = 88, IC 025 = 3), and cemiplimab (n = 5, IC 025 = 1.2); and anti-PD-L1 monotherapy (n = 53, IC 025 = 3) with atezolizumab (n = 36, IC 025 = 3), durvalumab (n = 11, IC 025 = 1.8), and avelumab (n = 6, IC 025 = 1.1) in monotherapy. Among cases with available data (n = 123), the median time to onset was 68 days (interquartile range [IQR]: 24.5–119.5), with a shorter delay observed in patients receiving dual immunotherapy compared to those treated with monotherapy. Among the cases for which data was available (n = 242), data recovery or partial recovery was reported in 58.3% (n = 141/242), while a fatal outcome was reported in 9% (n = 21). A significant reporting signal of GBS exists with the majority of ICI regimens employed in both monotherapy and dual immunotherapy.